Analisis Kesiapan Tenaga Pendidik dalam Menghadapi Era Society 5.0 di SMP Al-Muslim Sidoarjo - Rohmah, Suci Mashitatur; Musawir, Musawir (ISLAMIKA, 2024)
Amidst the rapid advancements in science and technology, particularly in the era of Society 5.0 that emphasizes the role of technology, the role of the education sector becomes pivotal in advancing the quality of human resources. Educators in the Society 5.0 era need to be equipped with digital skills and creative thinking abilities. Therefore, the objective of this research is to assess the readiness of educators to face the challenges of the Society 5.0 era. This study employs a qualitative method with a phenomenological approach, aiming to uncover and comprehend the unique phenomena experienced by individuals. Primary data is obtained through direct interviews with educators at SMP AL-MUSLIM Sidoarjo, while secondary data involves relevant books and journals. Data collection techniques include interviews, observations, and documentation. The research findings indicate that educators are prepared and matured to face the Society 5.0 era. This is evident in their competencies within domains such as teamwork, interpersonal and communication skills, problem-solving, critical thinking, soft skills and hard skills, as well as digital literacy. Their readiness is reflected in the implementation of human-centric and technology-based approaches in schools, encompassing digitization, CPS (Cyber Physical Human System) paradigm, and the utilization of Artificial Intelligence (AI). Factors influencing educators' readiness involve classroom management skills, mastery of teaching methods and tools, as well as the ability to plan and prepare for teaching.